Efficacy of in-person and telepractice-based extended Lee Silverman Voice Treatment LOUD on dysarthria and dysphagia in adults with cerebral palsy - Kyung Min Kim; Sang Ah Park; Seong Hye Hwang; Alyssia Park; Hyang Hee Kim; Jihye Hwang; Sung-Rae Cho (Digital Health)
Objective With advancements in digital health technologies, telepractice has become crucial for providing accessible medical interventions. Cerebral palsy (CP) frequently results in comorbidities including dysarthria and dysphagia, leading to restrictions in activities. This study evaluates the efficacy of both in-person and telepractice-based intensive voice therapy in improving speech, swallowing functions, and related quality of life measures in adults with CP. Methods The Lee Silverman Voice Treatment (LSVT) LOUD ® , a speech-behavior therapy, was administered to 16 CP subjects (9 men and 7 women; mean age = 43.4 ± 10.43 years) via in-person extended version of LSVT LOUD ® (LSVT-X), and telepractice program of LSVT-X (LSVT-X e-LOUD ® ). Outcomes, including maximum phonation time (MPT), voice intensity, diadochokinetic rate (DDK), Voice Handicap Index (VHI), swallowing quality of life (SWAL-QOL), and Videofluoroscopic Dysphagia Scale (VDS), were assessed pre- and post-treatment. Results Significant improvements were noted in speech functions: MPT ( p  = 0.006), voice intensity ( p  = 0.004), DDK /puh/ ( p  = 0.043), and DDK/puh-tuh-kuh/ ( p  = 0.031). Swallowing function improved significantly in the pharyngeal phase on the VDS. Quality of life measures showed improvement in physical ( p  = 0.003), emotional ( p  = 0.000), total score of VHI ( p  = 0.001), fear ( p  = 0.031), sleep ( p  = 0.013), fatigue ( p  = 0.003), and total score of SWAL-QOL ( p  = 0.019). These improvements were consistent in both LSVT-X and LSVT-X e-LOUD ® groups. Conclusions Both in-person and telepractice-based LSVT-X enhance speech, swallowing functions, and quality of life in adults with CP. LSVT-X e-LOUD ® can be utilized as a digital therapeutic intervention for dysphagia and dysarthria, offering accessible and flexible treatment options aligned with digital health advancements.